Implantación de un sistema contable en distribuidora “Loja Limpia”, de la ciudad de Loja, periodo junio – agosto / 2014 - Jadan Chalco, Tatiana Katherine (2015)
The present entitled thesis work: "INSTALLATION OF A COUNTABLE SYSTEM IN DISTRIBUIDORA "CLEAN LOJA", OF THE CITY DE LOJA, PERIOD JUNE - I WITHER / 2014" where is that of purchase and sale of articles as main activity, for this reason he/she intends the present work of Thesis with the purpose of facilitating the proprietor a countable tool to improve the economic yield of the business. During the development of the thesis like first point was analyzed the countable problems of the business, of there the necessity of the installation of the countable system arises; firstly a theoretical mark is built with own and necessary normative accountant for the correct pertinent countable development, then he/she left of the elaboration of an initial inventory based on all the goods, rights and obligations, subsequently he/she spent to the construction of the plan and manual the same one that was used in the whole countable practice until ending up concluding with the presentation of the States Financiers. As a result final of the elaboration of the Thesis, in the distribuidora LOJALIMPIA, you concludes that it doesn't have a countable system that facilitates the control of the bill merchandises since one runs the risk of managing a high stock or one can also run the watering that it is not had an up-to-date inventory, getting in this way that the business the economic profitability that the proprietor looks for doesn't toast; as well as the client's full satisfaction is not gotten